ECONOMIC VALUE ADDED (EVA) SEBAGAI ALAT UKUR KINERJA KEUANGAN PERUSAHAAN - NUGRAHINI KUSUMAWATI; NUR HAMIDAH (Jurnal Akademika, 2017)
This study aimed to analyze the financial performance  of five food and baverage industries. The period 2010-2014. The method used in this research is the method that includes aspects of Economic Value Added (EVA). Economic Value Aded (EVA) is a tool for analyzing the company finance performance. The result of this study indicate that five food industries have positive, its mean that five industries have value added, but PT. Siantar Top Tbk in 2014 have EVA < 0 because their Income Statement is lower than Cost that they must pay.Keywords: Financaial performance, Economic Value Added